UNVEILING THE PRACTICES OF RESEARCH PUBLICATION AMONG INDONESIAN ACADEMICS - Syaukani, Syaukani; Ismahani, Siti; Razak, Rafiza Abdul; Mukminin, Amirul (LPPM Universitas Jambi, 2025)
Research on poor-quality journals seems to be an inexhaustible study. The present study aims to understand the experiences of 3 Indonesian academics who published their scientific articles in disreputable journals. This phenomenology study was conducted within the framework of a qualitative approach. Data were collected by in-depth interviews academics. The study identified three key themes: Lack of Necessary Skills, Overestimation of Western Hegemony, and Acceptance of Fate. The findings indicated that some factors caused the academics to take shortcuts to get their articles published. The pressure to acquire the promotion to become a professor was the main factor influencing Indonesian academics to publish in these fast-turnaround journals. The findings highlight the need for academic institutions and policymakers to critically address the systemic pressures that drive scholars toward low-quality publishing outlets. Strengthening mentorship, providing training in academic writing, and reforming promotion policies to reward quality over quantity are essential to safeguard academic integrity. Furthermore, the study underscores the global implications of these issues, urging international academic bodies to collaborate in setting higher standards for research dissemination and evaluation practices.